1993
DOI: 10.1111/j.1476-5381.1993.tb13514.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug pharmacokinetics and neuropharmacokinetics in individual rats by repetitive withdrawal of blood and cerebrospinal fluid: milacemide

Abstract: The kinetics and metabolism of milacemide have been studied in an animal model which allows the simultaneous investigation of the temporal inter‐relationships of drugs and metabolites in blood (pharmacokinetics) and cerebrospinal fluid (CSF, neuropharmacokinetics) in individual freely moving rats. Milacemide dose‐dependently increased CSF glycine and glycinamide (intermediary metabolite) concentrations. This confirms that milacemide is a CNS glycine prodrug. Pretreatment with l‐deprenyl (2 mg kg−1), a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In order to study CSF pharmacokinetics, direct sampling of CSF with simultaneous serum sampling has been successfully used ( Patsalos et al ., 1992 ; Semba et al ., 1993 ; Lolin et al ., 1994 ; Walker et al ., 1998 ; Doheny et al ., 1999 ; Nagaki et al ., 1999 ). The limited accessibility of CSF and the impracticability of repeated sampling in humans have meant that most of these drug studies have been carried out in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study CSF pharmacokinetics, direct sampling of CSF with simultaneous serum sampling has been successfully used ( Patsalos et al ., 1992 ; Semba et al ., 1993 ; Lolin et al ., 1994 ; Walker et al ., 1998 ; Doheny et al ., 1999 ; Nagaki et al ., 1999 ). The limited accessibility of CSF and the impracticability of repeated sampling in humans have meant that most of these drug studies have been carried out in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Milacemide (2- n -pentylaminoacetamide) is considered to be a glycine prodrug. It was demonstrated that it readily crosses the BBB and its N -dealkylation by monoamine oxidase type B releases glycinamide, which is converted into glycine [ 37 ]. Yu et al [ 38 ] have recently shown that 2-propyl-1-aminopentane and 2-propylpentylglycinamide are readily deaminated by monoamine oxidase B and by semicarbazide-sensitive amine oxidase.…”
Section: Prodrug Bioconversion Strategiesmentioning
confidence: 99%
“…Milacemide (CP-1552S), a glycine pro-drug (glycine is an inhibitory neurotransmitter in the CNS), had minimal efficacy in patients with epilepsy even though it possessed anticonvulsant activity in animal models. A lack of understanding of the pharmacokinetic characteristics of milacemide may have been responsible for its demise [25].…”
Section: Aed Developmentmentioning
confidence: 99%